2017
DOI: 10.1021/acs.est.6b06557
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Diastereoisomeric and Enantiomeric Profiles of Hexabromocyclododecanes (HBCDs) in Adult Chicken Tissues, Eggs, and Hatchling Chickens

Abstract: ABSTRACT:The concentrations and enantiomer fractions (EFs) of α-, β-, and γ-hexabromocyclododecanes (HBCDs) were measured in chicken diet sources (soil and chicken feed), home-raised adult chicken (Gallus domesticus) tissues, eggs during incubation, and hatchling chicken tissues. HBCD concentrations were not detected−0.69 ng/g dry weight (dw) and 25.6−48.4 ng/g dw in chicken feed and soil, respectively. HBCDs were detected in all adult chicken tissues, except the brain, at median levels of 13.1−44.0 ng/g lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The α-/γ-isomer concentration ratios in fish from the two sampling sites from Lake Superior were 15.1 and 14.5, and for all the other sites the α-/γ-isomer concentration ratios were lower than 10. It has been shown that α-HBCDD predominates in ∑HBCDD concentrations in biotic samples, whereas γ-HBCDD is the predominant isomer in technical HBCDD mixtures and abiotic samples. , The underlying reasons leading to a given HBCDD isomer pattern in an abiotic or biotic sample can be due to, e.g., differential chemical-specific absorption and elimination, metabolism, and isomerization among three HBCDD isomers in biota. ,, Given the increasing percentage of α-HBCDD with time, some researchers have suggested that concentration ratios of HBCDD isomers can partly reflect recent inputs of technical HBCDD mixtures into the environment. , Interestingly, the lowest α-/γ-isomer concentration ratio (6.3, Figure ) was detected in fish from Lac Memphrémagog, and this location is near an area with historic manufacturing use of HBCDD.…”
Section: Resultsmentioning
confidence: 99%
“…The α-/γ-isomer concentration ratios in fish from the two sampling sites from Lake Superior were 15.1 and 14.5, and for all the other sites the α-/γ-isomer concentration ratios were lower than 10. It has been shown that α-HBCDD predominates in ∑HBCDD concentrations in biotic samples, whereas γ-HBCDD is the predominant isomer in technical HBCDD mixtures and abiotic samples. , The underlying reasons leading to a given HBCDD isomer pattern in an abiotic or biotic sample can be due to, e.g., differential chemical-specific absorption and elimination, metabolism, and isomerization among three HBCDD isomers in biota. ,, Given the increasing percentage of α-HBCDD with time, some researchers have suggested that concentration ratios of HBCDD isomers can partly reflect recent inputs of technical HBCDD mixtures into the environment. , Interestingly, the lowest α-/γ-isomer concentration ratio (6.3, Figure ) was detected in fish from Lac Memphrémagog, and this location is near an area with historic manufacturing use of HBCDD.…”
Section: Resultsmentioning
confidence: 99%
“…Enantiomeric selectivity of HBCD played key role in the toxicity and fate of HBCD stereoisomers in the environment. There is strong evidence that the environmental fates of HBCD are enantioselective ( Zhang et al, 2011 ; Zheng et al, 2017 ), while enantiomeric analysis has received relatively little attention in the literature on anaerobic degradation of HBCD. In this study, the occurrences of three pairs of enantiomers in the technical HBCD mixture, i.e., (±)α-, (±)β-, and (±)γ-HBCD, were confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…Different physiochemical properties (e.g., polarity, water solubility, and dipole moment) of these HBCD stereoisomers may lead to substantial differences in their toxicity, metabolism, and environmental fate ( Hakk et al, 2012 ). Indeed, there is increasing evidence for the diastereoisomer- and/or enantiomer-specific distribution and accumulation in various environmental media ( Yu et al, 2008 ; Haukås et al, 2009 ; Gao et al, 2011 ; Zhang et al, 2011 ; Wu et al, 2014 ), biota ( Janák et al, 2005 ; Zheng et al, 2017 ), and even in human body ( Shi et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The calculated bioaccumulation factors were 5.2, 3.6 and 9.2 in eggs, liver and abdominal fat, respectively. Zheng et al (2017) measured HBCDDs in diet sources and in chicken tissues in adult (n = 12) and hatchling chicken (n = 9). In feed samples, the highest HBCDD concentration measured was 0.69 ng/g dw while the highest concentration in soil was 28.8 ng/g dw.…”
Section: Transfer Of Hbcdds From Feed To Food-producing Animalsmentioning
confidence: 99%